Dynamicism in Yoruba Translation of the Quran - Badmus N. O. Abdul Azeez; Amidu Adinoyi Jimoh; Issah Zubairu Achara; Abubakar Yusuf Abdullahi (International Journal of Integrative Sciences, 2023)
The appearance of a published complete translation of the Qur'an into Yoruba language was a recent occurrence phenomenon compared to the early contact of Islam with Yorubaland. This has been attributed to the fact that the early Imams and Arabic and Islamic teachers concentrated on the teaching of Arabic Language. This article discussed the activities of the Qur'an translators and examined the impact of that on the target audience. A number of grey areas in the Yoruba translations are brought to the fore for possible adjustment. The article employed historical and analytical methods in gathering information from primary and secondary sources. The translation of the Qur'an into Yoruba language remains a major intellectual contribution of the Yoruba Muslim scholars to the dissemination of Islamic teachings. However, the translators are yet to take cognizance of the conditions and prerequisites of translating the Qur'an. This has led to adverse effects on most of the translations of the Qur'an into Yoruba. The article has also brought to focus some improvements in translation of the Qur'an including the nature of the contributions, their merits and demerits. The study proposes a template for improvement so that subsequent translations will not only address contemporary needs but also benefit from an extensive circulation of the Quranic message